Migration and the Gendered Origin of Migrant Networks among Couples in Mexico - Creighton, Mathew J (Social science quarterly, 2013)
OBJECTIVES: We investigate how the matrilineal vs. patrilineal origin of Mexican couples' migrant networks are associated with the aspirations to migrate and the subsequent migration behavior of each spouse